Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1007/s00330-017-4973-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a prognostic model incorporating texture analysis derived from standardised segmentation of PET in patients with oesophageal cancer

Abstract: ObjectivesThis retrospective cohort study developed a prognostic model incorporating PET texture analysis in patients with oesophageal cancer (OC). Internal validation of the model was performed.MethodsConsecutive OC patients (n = 403) were chronologically separated into development (n = 302, September 2010-September 2014, median age = 67.0, males = 227, adenocarcinomas = 237) and validation cohorts (n = 101, September 2014-July 2015, median age = 69.0, males = 78, adenocarcinomas = 79). Texture metrics were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 33 publications
(43 reference statements)
1
68
0
Order By: Relevance
“…Similarly, in a study of 65 patients Paul et al found that a model incorporating GLCM homogeneity was a predictor of response (with an AUROC value of 0.823) but not of survival [29]. However, in a larger study with 403 patients, Foley et al found that total lesion glycolysis, histogram energy and kurtosis were independently associated with overall-survival [30].…”
Section: F-fdg Pet Radiomicsmentioning
confidence: 98%
“…Similarly, in a study of 65 patients Paul et al found that a model incorporating GLCM homogeneity was a predictor of response (with an AUROC value of 0.823) but not of survival [29]. However, in a larger study with 403 patients, Foley et al found that total lesion glycolysis, histogram energy and kurtosis were independently associated with overall-survival [30].…”
Section: F-fdg Pet Radiomicsmentioning
confidence: 98%
“…[88] One large, single centre study developed and internally validated a prognostic model including PET radiomics and found that model performance for overall survival improved compared to traditional clinical factors. [89] One critical aspect and potential limitation of radiomics is the reliability and reproducibility of these features. Much radiomics research is now concentrating on defining stable features for future application.…”
Section: Radiomicsmentioning
confidence: 99%
“…[14] A previously published prognostic model had been developed and internally validated in patients with esophageal cancer. Details of model development have been provided in Foley et al [11] Briefly, the prognostic model had only been evaluated by same-centre internal validation in patients managed by the South-East Wales Regional Upper Gastrointestinal (GI) Cancer Multi-Disciplinary Team (MDT), United Kingdom. A suitable independent cohort was not accessible at the time of publication.…”
Section: Methodsmentioning
confidence: 99%
“…[9] Post-reconstruction harmonisation methods have been proposed to adjust for these differences, thus promoting standardised research between centres. [10] The primary aim of this study was to test the generalizability of a UK single-centre esophageal cancer prognostic model incorporating radiomic features [11] firstly preharmonisation, then post-harmonisation, against a cohort of esophageal cancer patients treated exclusively with neo-adjuvant chemoradiotherapy (NACRT) according to the Dutch NACRT plus surgery versus surgery alone for oesophageal/junctional cancer (CROSS) trial regimen. [12] A widely generalizable prognostic model incorporating radiomic features of primary tumours might offer clinicians complimentary data beyond traditional prognostic factors that will assist treatment decision making and risk stratification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation